APLIKASI LOGIKA FUZZY UNTUK PERAMALAN BEBAN LISTRIK JANGKA PENDEK MENGGUNAKAN MATLAB - Effendi, Hansi (Sainstek, 2009)
This research is conducted to apply Fuzzy Logic which is implemented in short term load forecasting. Data that is used for short term load forecasting are historical load data and temperature data. The data is analyzed to learn the load characteristic of Sumbar System which is used as references for making rules in Fuzzy Logic. The Fuzzy Logic model is made using fuzzy logic toolbox that is provided by Matlab. The forecasting result is compared with actual load. It is seen from experiment that the advantage of Fuzzy Logic is its rules that are made from supplied data. Keyword :       Fuzzy Logic, load forecasting, rules.